Barriers to healthcare access and continuity of care among Ukrainian war refugees in Europe: findings from the RefuHealthAccess study - Kardas, Przemyslaw; Mogilevkina, Iryna; Aksoy, Nilay; Ágh, Tamas; Garuoliene, Kristina; Lomnytska, Marta; Istomina, Natalja; Urbanaviče, Rita; Wettermark, Björn; Khanyk, Nataliia (Frontiers in Public Health, 2025)
IntroductionThe Russian invasion of Ukraine displaced over 14 million people. By 2024, around 6 million Ukrainian refugees settled in Europe under the EU Temporary Protection Directive, providing permit of residence, work and health care. This influx strained European healthcare systems, particularly in addressing acute injuries. As the stay of refugees in EU countries prolongs, the management of chronic conditions becomes increasingly important. However, there is limited information available about Ukrainian refugees' access to various healthcare services.AimThe aim of this study was to evaluate perceived accessibility of healthcare services in Europe for Ukrainian war refugees and to identify barriers to healthcare access, in order to inform improvements in healthcare provision.MethodsA cross-sectional online survey was conducted across Europe from July 2023 to April 2024, targeting adult Ukrainian war refugees. Survey explored areas defined as key health care needs. Descriptive, parametric and non-parametric statistical analysis methods were employed in data analysis.ResultsOf 659 respondents, 550 (83.4%) were included in the final analysis due to having reported need to use healthcare services in the past year. The most prevalent needs included dental care (82.9%), prescription medication (81.6%), care for acute (78.4%), and chronic conditions (64.0%). Perceived access to care varied across services, with vaccinations rated highest, while chronic condition care rated lowest. Around ¼ of respondents reported that they had to temporarily return to Ukraine for services not available in the countries where they stayed, these being mostly dental and gynaecologic care. The most prevalent barriers reported were long waiting times (64.2%), information barriers (55.5%), and high service costs (49.1%).DiscussionThe survey identified several barriers in the access to healthcare system for Ukrainians, particularly for chronic conditions care. Some barriers may be subjective, relating to limited access to information. However, others point to potential shortcomings within national healthcare systems, suggesting areas that require further review and improvement.ConclusionsAddressing language barriers, improving information dissemination, and enhancing chronic condition management were identified as crucial for improving healthcare access for Ukrainian war refugees. Coordinated strategies are needed to support refugees and ensure the sustainability of host healthcare systems.